Beginning Teacher Programs - Furtwengler, Carol B. (Education Policy Analysis Archives, 1995)
This article reports the findings from the conduct of a 50- state survey to determine the status of state requirements and state components of beginning teacher programs instituted from 1983 to 1992. The article discusses the implementation of beginning teacher programs during the 1980s reform movement and describes the methodology used for the study. An analysis of seven state policy issues derived from an interpretation of the information about beginning teacher programs is provided, and four major themes identified in beginning teacher programs are presented. Appendices include detailed state-by-state information about beginning teacher programs and an annotated reference list of state materials and publications related to these programs.